Extensive Reading Online while Writing Academic Articles: An Embedded Mixed Method Study - Rahmawati, Henny; Dzulfikri, Dzulfikri (Universitas Jambi, Indonesia, 2022)
Writing an academic article is a must for scholars to fulfil their academic demands. Departed from the input hypothesis proposed by Krashen (2011) saying that input knowledge very matters in language learning and so as in writing an academic article, reading has undoubtedly been agreed to gain language inputs. The pandemic Covid-19 outbreak, recently, forces a face-to-face meeting to the fully virtual mode of learning. Hence, the lecturers are getting another challenge to find another way to cope with online learning. To fill this gap, this study, then, aimed to investigate whether the er-central, an online extensive reading platform by which the students can acquire the input knowledge, can positively contribute to writing scholarly articles in terms of the students’ attitudes towards reading per se. The participants were sophomores of a private university in Indonesia consisting of twenty-seven students taking a required writing course in eight meetings conducted fully virtually, at the end of which a scholarly article must be an outcome for each student. The method used in this study was a mixed-method, the participants were divided into two groups, experimental and control group—seventeen and ten respectively. The data gathered were then both qualitatively and quantitatively analysed to gain the most appropriate information. The result showed that the use of er-central did not significantly affect, though it’s very helpful in improving the students’ attitudes towards reading when writing academic articles. Reflecting on this study, to attain better results the lecturers and future researchers as well should focus more on how the students enjoy reading and on how to promote purposeful reading that is reading for writing an academic article.